Clinical evaluation of "componeers" and direct composite veneers using minimally invasive enamel preparation technique: In vivo study - Parag Dua; Sanjay Manohar Londhe; Gaurav Dua; Atul Kotwal; Sachin Gupta (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study was to evaluate the clinical behavior of prefabricated componeers and direct composite veneering. The objective of the study was to compare the changes in color, surface texture, marginal integrity, and gingival response for componeers and direct composite veneers. Settings and Study Design: This was an in vivo, comparative study. Materials and Methods: Ten patients indicated for anterior veneers were selected and divided into Groups A and B of five patients each. Group A was restored with componeers and Group B with direct composite veneers. Both the groups were compared for color changes, surface textural changes, marginal integrity, and gingival response, starting immediately post veneering and at 3, 6, 9, and 12 months subsequently. Statistical Analysis Used: Friedman's two-way analysis of variance and Mann-Whitney test were used for statistical analysis. Results: Results for color ranged from excellent to good with minimal color changes post veneering. Overall, "gingival response," in both the groups, showed statistically significant differences in mean rank scores (P ≤ 0.05). The data depicted an improvement in gingival response for all patients during the period of the study. Surface textural changes were significant only for maxillary right canine and maxillary left lateral incisor (P = 0.024 and 0.039, respectively) in both the groups. Maxillary right canine in both the groups showed significant changes in marginal integrity. Intergroup comparison of gingival response, surface texture, and marginal integrity depicted no significant difference between the groups (P > 0.05). Conclusions: This study concluded that the intergroup comparison of componeers and direct composite veneers for the parameters, gingival response, surface texture, and marginal integrity did not depict any significant differences. Both the groups displayed minimal changes in color, surface texture, and marginal integrity and improved gingival response.